2019
DOI: 10.1002/cncy.22101
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and surgical outcomes of Hürthle cell lesions in FNAs of the thyroid: A multi‐institutional study in 6 Asian countries

Abstract: BACKGROUND: Hürthle cell-rich nodules (HCNs) encompass non-neoplastic to malignant lesions. There is paucity of literature on the frequency distribution of HCNs among Bethesda categories, histologic follow-up, risk of malignancy (ROM), and risk of neoplasia (RON). The objective of this retrospective, multi-institutional study was to determine the prevalence of the cytologic diagnostic category and surgical outcomes of patients with HCN. METHODS: Nine tertiary health centers representing 6 Asian countries parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…The overall rate of thyroid malignancy was 15.1%; this included oncocytic variants of other types of thyroid malignancy. This is consistent with rates previously described 10‐14 . Of the patients who underwent an initial hemithyroidectomy and were found to have malignancy, 23.1% were found to have a contralateral malignancy after completion thyroidectomy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The overall rate of thyroid malignancy was 15.1%; this included oncocytic variants of other types of thyroid malignancy. This is consistent with rates previously described 10‐14 . Of the patients who underwent an initial hemithyroidectomy and were found to have malignancy, 23.1% were found to have a contralateral malignancy after completion thyroidectomy.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with rates previously described. [10][11][12][13][14] Of the patients who underwent an initial hemithyroidectomy and were found to have malignancy, 23.1% were found to have a contralateral malignancy after completion thyroidectomy. These findings can be incorporated into patient counseling and management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lee et al [32] reported that 60% of surgical cases with HTC were designated as malignancies based on frozen sections. A meta-analysis for Hürthle cell lesions in thyroid FNA in nine institutions from six Asian countries revealed that there was interinstitutional variation in the cytologic interpretation of Hürthle cell morphology and in Bethesda categorization [33]. Hürthle cell-rich aspirates were most frequently categorized as AUS/FLUS, followed by FN/SFN.…”
Section: Fine-needle Aspiration Cytology and Intra-operative Frozen Smentioning
confidence: 99%